An attempt to identify and estimate the subsurface groundwater discharge in the south east coast of India - Chidambaram, S.; Nepolian, M.; Ramanathan, A.; Sarathidasan, J.; Thilagavathi, R.; Thivya, C.; Prasanna, Mohan Viswanathan; Srinivasamoorthy, K.; Jacob, N.; Mohokar, H. (Elsevier BV, 2017)
An attempt has been made to study the subsurface groundwater discharge (SGD) in the coastal Cuddalore region of south east India. Measurement for Radon, water level, Electrical Conductivity (EC) and pH in surface water for a total of twenty hours by hourly interval has been attempted and further correlated with tidal values calculated by WX Tide 32 software. The SGD measurements were made by using a modified seepage meter. The study reveals a match with water level variation and tide with minor variation due to influx of surface water. Saline discharges, fresh groundwater discharges and surface water mixing processes were identified along the coast. Lower SGD (37.24–79.16 cm/day) was observed during fresh groundwater discharge.